Career Choices and Career Progression of Junior Doctors in Dermatology: Surveys of UK Medical Graduates - Atena Barat; Michael J. Goldacre; Trevor W. Lambert (Dermatology Research and Practice)
Objective. To report UK-trained doctors’ career choices for dermatology, career destinations, and factors influencing career pathways. Methods. Multicohort multipurpose longitudinal surveys of UK-trained doctors who graduated between 1974 and 2015. Results. In all, 40,412 doctors (58% of graduates) responded in year 1, 31,466 (64%) in year 3, and 24,970 (67%) in year 5. One year after graduation, 1.7% of women and 0.6% of men made dermatology their first choice but by five years after graduation the respective figures were 1.0% and 0.7%. Compared to their predecessors, its popularity fell more substantially from years 1 to 5 among recent graduates (2005–15), particularly for women (from 2.1% in year 1 to 0.8% in year 5) compared with a fall from 0.8% to 0.5% among men. The most important factor influencing dermatology choice was “hours/working conditions”: in year one, 69% regarded this as important compared with 31% of those choosing other hospital physician specialties. Only 18% of respondents who chose dermatology at year 1 eventually worked in it; however, almost all practising dermatologists (94%), 10 years after qualifying, had made their future career decision by year 5. Conclusion. Dermatology is popular among female UK graduates. Most dermatologists made their career decision late but decisively.